Outbreak investigation of Serratia marcescens bloodstream infection in an obstetric ward for high-risk pregnant women - Seulki Kim; Sunah Jung; Dong Hyung Lee; Chulhun L. Chang; Moonsuk Bae; A Reum Kim; Su Jin Lee; Seungjin Lim (BMC Infectious Diseases, 2024)
Abstract Background Serratia marcescens is a gram-negative bacterium that is widespread in the environment. S. marcescens bacteremia can be fatal during pregnancy and cause persistent chorioamnionitis. This study reports an outbreak of Serratia marcescens bloodstream infection (BSI) among high-risk pregnant women in an obstetric ward. The purpose of this study is to report our experience with the usefulness of the ATP test in hospital environmental management and to confirm that bloodstream infections of patients with the same strain were correlated by WGS testing. Methods This retrospective study collected the data of inpatients with S. marcescens bacteremia in obstetric ward for high-risk pregnant women from August 22, 2021, to October 14, 2021. We performed: an adenosine triphosphate (ATP) bioluminescence test in the environment with a high-contact area; environmental culture; on-site monitoring and staff education; and whole-genome sequencing (WGS) to evaluate genetic relationships among S. marcescens isolates. Results S. marcescens BSI occurred in four consecutive patients. None of the patients had central venous catheters. An ATP bioluminescence test revealed that high-contact areas and areas for injection preparation were not clean (≥ 1000 relative light units). However, S. marcescens was not identified in the environmental cultures, likely due to intensive environmental cleaning and discarding of potentially contaminated specimens before the culture test. On-site monitoring and education were conducted for 1 month. There were no further reports of BSI until 6 months after the last patient was discharged. WGS performed on three isolates from three patients indicated that the isolated S. marcescens was likely from the same strain. Conclusions We controlled an S. marcescens outbreak by improving environmental cleaning as well as education of and behavior changes in healthcare workers. Using the ATP bioluminescence test can provide feedback on environmental cleaning and education. WGS played a role in determining the spread of BSI caused by the same strain.